Plant-parasitic nematodes in Nova Scotia vineyards - Forge, Thomas; Munro, Paige; Wright, Harrison; Moreau, Debra (Phytoprotection, 2022)
Plant-parasitic nematode populations were analyzed from composite soil samples collected from 62 vineyard blocks throughout Nova Scotia in 2018 and 2019. Nematode groups of potential concern that were found included ring nematodes (family Criconematidae), dagger nematodes (Xiphinema spp.), and root-knot nematodes (Meloidogyne spp.). Ring nematodes were overall the most widespread and abundant group of plant-parasitic nematodes, recovered from 79% of blocks with an overall average population density of 114 nematodes per 100 cm3 soil. Ring nematodes tended to be more abundant in older blocks. DNA sequence analyses of a subset of the ring nematode populations confirmed the presence of Mesocriconema xenoplax, which is the species known to be damaging to and most widely associated with grapevine globally. The analyses indicated that Criconema permistum was also present, notably in samples with the greatest ring nematode population densities. The results indicate that ring nematodes could be affecting the health of Nova Scotia vineyards, particularly in the future as populations continue to develop in relatively young vineyards and as older blocks are replanted. Additional research is needed to delineate the distribution of M. xenoplax vis-à-vis other species and to experimentally assess the host-parasite relationship between C. permistum and grapevine.